The Effects of Shrimp Pond Waste on Water Quality of Patas Village as A Center Of Seaweed (Eucheuma spinosum) Cultivation - Negara, I Ketut Wija; Saraswati, Suprabadevi Ayumayasari; Wijayanti, Ni Putu Putri (Advances in Tropical Biodiversity and Environmental Sciences, 2018)
The intensive farming of vannamei shrimp in Patas village release waste that affected the water quality for seaweed cultivation. The aims of this study were to investigate the effects of shrimp pond waste to water quality and growth of seaweed Eucheuma spinosum in Patas village. The research located in Patas village, Gerokgak district, Buleleng regency, Bali province, during the plantation cycle (45 days) from July to September 2017. The collected data consist of total N, total P, Nitrate (NO3 - ), Ammonium (NH4 + ), and Phosphat (PO4 3- ). The results showed the average weight of seaweed near the shrimp ponds was 5.85% g with 0.15% g increment, while at the far location from shrimp ponds was 7.05% g with 0.41% g increment. Its indicated that the Eucheuma spinosum cultivated in far location has a better yield than the near location from shrimp ponds. The Chlorine content in shrimp pond waste affecting the seaweed growth and water quality, such as salinity, pH, DO, Nitrate, and Phosphat.